2014
DOI: 10.1007/s10142-014-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel and conserved heat-responsive microRNAs in wheat (Triticum aestivum L.)

Abstract: MicroRNAs (miRNAs) are small endogenous RNAs of ~22 nucleotides that have been shown to play regulatory role by negatively affecting the expression of genes at the post-transcriptional level. Information of miRNAs on some important crops like soybean, Arabidopsis, and rice, etc. are available, but no study on heat-responsive novel miRNAs has yet been reported in wheat (Triticum aestivum L.). In the present investigation, a popular wheat cultivar HD2985 was used in small RNA library construction and Illumina Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 56 publications
9
90
0
3
Order By: Relevance
“…Sequencing profiles revealed that most miRNA families responded similarly to both the stressors (drought or heat) while a fewmiRNA families showed stress-specific response, i.e., induced or repressed only under drought or heat in switchgrass ( Table 2). The altered expression of several miRNAs following drought or heat in this study was largely in agreement with several earlier reports that studied miRNA responses to stress conditions ingrasses[40,41, [53][54][55][56][57][58][59][60][61][62][63][64][65][66].Nevertheless, there are alsoinstances in which our study did not correspond with some of the earlier reports. For instance,drought stress repressed the expression of miR166 in wheat [53], rice [57] and sugarcane [63] while we found it is induced in switchgrass.Drought downregulated the expression of miR167 and miR168 in switchgrass [40] andmiR168 in rice [57]butthese miRNAs are found to be up-regulated by drought in this study.The miR396 levels were repressed in wheat [53],rice [57] and sugarcane [63]under drought but it is up regulated under drought in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sequencing profiles revealed that most miRNA families responded similarly to both the stressors (drought or heat) while a fewmiRNA families showed stress-specific response, i.e., induced or repressed only under drought or heat in switchgrass ( Table 2). The altered expression of several miRNAs following drought or heat in this study was largely in agreement with several earlier reports that studied miRNA responses to stress conditions ingrasses[40,41, [53][54][55][56][57][58][59][60][61][62][63][64][65][66].Nevertheless, there are alsoinstances in which our study did not correspond with some of the earlier reports. For instance,drought stress repressed the expression of miR166 in wheat [53], rice [57] and sugarcane [63] while we found it is induced in switchgrass.Drought downregulated the expression of miR167 and miR168 in switchgrass [40] andmiR168 in rice [57]butthese miRNAs are found to be up-regulated by drought in this study.The miR396 levels were repressed in wheat [53],rice [57] and sugarcane [63]under drought but it is up regulated under drought in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…For example, miR167 and miR529expression was downregulated in response to heat in rice [56], whereas we found upregulation in switchgrass. Likewise, miR393 was down regulated by heat in wheat [65]whereas it was upregulated in this study. Such discrepancies between different species or even within switchgrass could be attributed to a variety of factors such as differences in stress imposition,stress intensity, stress duration, age of the treated plants andtissue sources (leaves vsseedlings) or even speceis-specific responses.…”
Section: Discussionsupporting
confidence: 62%
“…Predictions on yield reductions in wheat on account of the climate change are frightening. However, it is difficult to identify novel SAGs, when the genomic information is not available (Kumar et al, 2014b). High-throughput NGS is, however, currently contributing significantly in the identification of novel genes associated with the biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Drought-associated miRNAs include 11 in cowpea (Barrera-Figueroa et al, 2011), five in maize (Sheng et al, 2015), 18 each in rice (Barrera-Figueroa et al, 2012) and sorghum (Katiyar et al, 2015), and 71 in durum wheat (Liu et al, 2015). In contrast, the heat stress responsive miRNAs include eight in common bean (Jyothi et al, 2015), 11 and 26 in rice (Liu et al, 2017; Mangrauthia et al, 2017), and 6 and 12 in wheat (Xin et al, 2010; Kumar et al, 2015). Changes in miRNAs under stress correlate well with increased expression of stress-related genes in tolerant genotypes.…”
Section: Synthesismentioning
confidence: 99%
“…For example, Liu et al (2017) reported eight target genes that correspond with 26 miRNAs within the four QTL regions associated with heat stress in heat-tolerant rice. This relationship of miRNAs with their target genes, however, may not be one-to-one (i.e., negative or positive) and may vary between miRNAs of the same gene family or even for the same target miRNAs at various development stages (Lopez-Gomollon et al, 2012; Zhang et al, 2012; Kumar et al, 2015). Identification of differentially abundant miRNAs in stress-tolerant germplasm may thus provide molecular evidence that miRNAs contribute to stress tolerance and so are good candidates for enhancing stress tolerance in crops by transgenic breeding.…”
Section: Synthesismentioning
confidence: 99%